نقل الميت من بلد إلى بلد في آراء العلماء: Moving Corpses From One Country to Another According to the Opinion of Ulama - Rosmita; Lisdiana (البصيرة: مجلة الدراسات الإسلامية, 2025)
This research discusses the law of moving corpses from one country to another. The first goal is to find out the laws of moving corpses from one country to another. The second is knowing the law of moving bodies from a cemetery to another cemetery. The scientific approach used by researchers consists of the following: inductive approach, deductive approach, and comparative approach. The results of this research are: first, the law of moving corpses from one country to another. Maliki believes that it is permissible to transport them as long as it does not result in a violation of sanctity, ugliness, or change, while Hanbali says it is makruh to move them without any intention, and Hanafi says it is makruh to move them beyond a distance of 2 km. Meanwhile, Syafi'i has two opinions, namely the first opinion that the law is haram and the second opinion that it is makruh. Second, the law of moving a body from one grave to another is essentially haram, unless it is forced, for example, to be buried in a mosque or on confiscated land, in which case it must be moved, namely for the benefit of the Muslim community, for example, the expansion of a mosque, then this is permissible.